2017
DOI: 10.4236/jwarp.2017.96040
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Groundwater Quality around a Major Mining Company in Southern Sierra Leone

Abstract: Ensuring availability and sustainable management of water and sanitation for all by 2030 is Goal 6 of the Sustainable Development Goals (SDGs). Since developing countries especially in Africa would struggle to meet this target, this study was conceived. Hence, the study was designed to assess the water quality for physiochemical parameters around a mined out site in southern Sierra Leone with the view to determine their levels, determine related associations among indicators and explore environmental forensic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
4
2
Order By: Relevance
“…Findings for NO 3 in this study is in sharp contrast with a similar study in Koira-Joda mining area in India where all water samples were highly contaminated with Nitrate even though their analysis was based on the Indian standard (IS) 10500 (2012) [32]. This observable pattern was different for a recent study in the same area that considered ground water quality which reported elevated levels of nitrate across sampling locations [20]. In the case of fluoride, there was a low detection of this indicator in water samples from GS, DMT, DT, WPT, and at three sampling sites from LDMT.…”
Section: (Mg/lcontrasting
confidence: 99%
See 4 more Smart Citations
“…Findings for NO 3 in this study is in sharp contrast with a similar study in Koira-Joda mining area in India where all water samples were highly contaminated with Nitrate even though their analysis was based on the Indian standard (IS) 10500 (2012) [32]. This observable pattern was different for a recent study in the same area that considered ground water quality which reported elevated levels of nitrate across sampling locations [20]. In the case of fluoride, there was a low detection of this indicator in water samples from GS, DMT, DT, WPT, and at three sampling sites from LDMT.…”
Section: (Mg/lcontrasting
confidence: 99%
“…In addition, it has been reported that variance in turbidity values along a surface water is strongly associated with stream hydrology and land use pattern [23]. The findings for this indicator is in disagreement with a recent study on ground water quality conducted in the same area where more than 80% of values were in conformity with WHO value [20]. However, the pattern of turbidity values across locations in the study area of this current study is in agreement with an earlier study on turbidity in different watersheds in New Mexico, USA [23].…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations